ASSESSMENT OF EFFECTIVE IMPLEMENTATION OF PUBLIC PROCUREMENT POLICIES ON THE PERFORMANCE OF 4-STAR HOTELS IN GABORONE (A CASE OF PEERMONT MONDIOR HOTEL) - Getenga, Thomas; Mburu, David (International Journal of Supply Chain Management, 2022)
Purpose: Procurement policies implementation has been recognized as the most difficult challenge affecting the government funded four-star hotel hotels in Gaborone, Botswana, and their attempts to attain economic growth of the country. Thus, this study was conducted to assess the effective implementation of public procurement legislation as well as the performances of Gaborone's four-star hotel. A case of Peermont Mondior Hotel. Methodology: The study used descriptive research design, and applied a census design since the target population of 43 respondents was a manageable number. Findings: According to the analysis, payment policies, access to information policies and tendering policies had a positive and significant relation with on the performance of Peermont Mondior Hotel, with a P-value of less than 0.05. However, procurement of consultancy policies was not significant. Unique contribution to theory, practice, and policy: The study recommends 4-star hotels to continually implement public procurement policies from the government in order to improve their performance. Further the government of Botswana should redefine payment policies, increase funding in the procurement of consultancy policies and enhance continuous technology innovation in support of the 4-star hotels performance.